2019
DOI: 10.3389/fmicb.2019.02761
|View full text |Cite
|
Sign up to set email alerts
|

Differently Pre-treated Alfalfa Silages Affect the in vitro Ruminal Microbiota Composition

Abstract: Alfalfa (Medicago sativa L.) silage (AS) is an important feedstuff in ruminant nutrition. However, its high non-protein nitrogen content often leads to poor ruminal nitrogen retention. Various pre-ensiling treatments differing with respect to dry matter concentrations, wilting intensities and sucrose addition have been previously shown to improve the quality and true protein preservation of AS, and have substantial effects on in vitro ruminal fermentation of the resulting silages. However, it is unknown how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…The relative abundances of Ruminococcaceae NK4A214 group, Ruminococcaceae UCG-002, Ruminococcaceae UCG-005, Roseburia, Bifidobacterium, and Christensenellaceae R-7 group were significantly increased in ALK, PECT1, PECT2, and CELL (Figure 4). Research has shown that genera of family Ruminococcaceae contain major (hemi)cellulolytic and pectinolytic species (Pettipher and Latham, 1979;Nyonyo et al, 2014;Hartinger et al, 2019a). Thus, microbes from family Ruminococcaceae play an important role in degrading (hemi)cellulose and pectin in their activity against recalcitrant fiber (Shinkai and Kobayashi, 2007;Flint et al, 2008).…”
Section: Community Structure Of Swine Microbiota Fed With Differentlymentioning
confidence: 99%
“…The relative abundances of Ruminococcaceae NK4A214 group, Ruminococcaceae UCG-002, Ruminococcaceae UCG-005, Roseburia, Bifidobacterium, and Christensenellaceae R-7 group were significantly increased in ALK, PECT1, PECT2, and CELL (Figure 4). Research has shown that genera of family Ruminococcaceae contain major (hemi)cellulolytic and pectinolytic species (Pettipher and Latham, 1979;Nyonyo et al, 2014;Hartinger et al, 2019a). Thus, microbes from family Ruminococcaceae play an important role in degrading (hemi)cellulose and pectin in their activity against recalcitrant fiber (Shinkai and Kobayashi, 2007;Flint et al, 2008).…”
Section: Community Structure Of Swine Microbiota Fed With Differentlymentioning
confidence: 99%
“…Indeed, cell wall degradation by AF can be higher than by bacteria under certain in vitro conditions [ 25 , 26 ] but quantifying the exact fungal contribution to fiber breakdown in the rumen is difficult. However, several in vitro and in vivo studies demonstrated the association between AF and an improved fiber degradability [ 25 , 26 , 27 , 28 ], which is also suggested by recent in vitro data from Ma et al [ 26 ]. These authors investigated the impact of co-culturing methanogens with either AF or bacteria on in vitro degradation of rice and wheat straw, observing higher dry matter and fiber degradation in the presence of AF, the extent of which was similar to lignocellulose breakdown by whole ruminal content.…”
Section: Current Perception Of Anaerobic Fungi In Ruminant Nutritimentioning
confidence: 74%
“…Amplicon libraries of the V4 region of the 16S rRNA were generated from the cDNA synthetized from single gut and water samples, using barcoded and modified F515-806R primers [ 86 ]. The PCRs were performed in triplicate, purified, and quantified as previously described [ 29 ]. Purified PCR amplicons were pooled in an equimolar mix and sent for library preparation and sequencing using the Illumina NovaSeq 6000 S2 PE150 XP technology at Eurofins Genomics Germany GmbH (Eurofins Genomic, Ebersberg, Germany).…”
Section: Methodsmentioning
confidence: 99%